2014
DOI: 10.1521/soco.2014.32.5.409
|View full text |Cite
|
Sign up to set email alerts
|

Network Structure Moderates Intergroup Differentiation of Stereotyped Rumors

Abstract: The role of network structure in intergroup differentiation-the bipolarization of stereotypes that are defensive (ingroup-positive/outgroup-negative) and non-defensive (outgroup-positive/ingroup-negative)-was investigated using a Dynamic Social Impact Theory (DSIT) framework. Three computermediated laboratory social network experiments were pooled to test the interaction of network clustering (cliquish structure) and segregation (personal network homogeneity) on intergroup differentiation. Democrats and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The current political landscape of social media has particularly negative implications for the spread of misinformation. Experiments have shown that high segregation and clustering within a community increase the polarization of opinions in rumors as well as belief perseverance (DiFonzo et al, 2013(DiFonzo et al, , 2014. Therefore, it is critical to understand how political rumors diffuse and are debunked in a contemporary media environment where users can easily filter and choose their information sources.…”
Section: Introductionmentioning
confidence: 99%
“…The current political landscape of social media has particularly negative implications for the spread of misinformation. Experiments have shown that high segregation and clustering within a community increase the polarization of opinions in rumors as well as belief perseverance (DiFonzo et al, 2013(DiFonzo et al, , 2014. Therefore, it is critical to understand how political rumors diffuse and are debunked in a contemporary media environment where users can easily filter and choose their information sources.…”
Section: Introductionmentioning
confidence: 99%
“…Psychometric analysis. To understand the if there are behavioral changes in terms of content generated and shared by users with increasing activity, we use the Linguistic Inquiry and Word Count (LIWC) dictionary, 9 which identi es emotions in words [18]. We measure the fraction of tweets containing the LIWC categories: anger, sadness, posemo, negemo, and anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…DiFonzo et al [9] report on a user study that shows how the network structure a ects the formation of stereotypes when discussing controversial topics. They nd that segregation and clustering lead to a stronger "echo chamber" e ect, with higher polarization of opinions.…”
Section: Related Workmentioning
confidence: 99%
“…The particular configurations of individuals within a social network space, which can assume ribbon, torus or family forms (Latané & L'Herrou, 1996), might have a direct impact on communication processes and rumour transmission in particular (DiFonzo & Bordia, 2007c). Recent studies on the basis of computer‐mediated social network experiments have demonstrated that changes to the configuration of a social network and specifically to the network arrangement of individuals within a social space had a direct influence on belief in a rumour as well as the transmission and persistence of the rumour (DiFonzo et al, 2013; DiFonzo et al, 2014).…”
Section: Towards a Socially Situated Approach To Rumour Transmissionmentioning
confidence: 99%